2014
DOI: 10.1017/s0007114513004029
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of dietary arginine, leucine and protein levels on fatty acid composition and gene expression in the muscle and subcutaneous adipose tissue of crossbred pigs

Abstract: The cumulative effects of dietary arginine, leucine and protein levels on fat content, fatty acid composition and mRNA levels of genes controlling lipid metabolism in pig longissimus lumborum muscle and subcutaneous adipose tissue (SAT) were investigated. The experiment was performed on fifty-four intact male pigs (Duroc £ Pietrain £ Large White £ Landrace crossbred), with a live weight ranging from 59 to 92 kg. The pigs were randomly assigned to one of six experimental treatments (n 9). The treatments followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 39 publications
5
40
2
2
Order By: Relevance
“…Dietary proteins may play a role in mechanisms affecting fatty acid composition (Bjørndal et al, 2013;Leveille, Tillotson, & Sauberlich, 1963). The amino acid composition of the diet has been shown to influence lipogenesis and desaturation, as tyrosine down-regulates hepatic D6 activity (Peluffo, Nervi, Gonzalez, & Brenner, 1984), and arginine and leucine can regulate the gene expression of Scd1 and Fas in muscle and adipose tissue (Madeira et al, 2014). Here, the amino acid composition did not differ to a large extent since they were all dominated by amino acids from casein.…”
Section: Discussionmentioning
confidence: 82%
“…Dietary proteins may play a role in mechanisms affecting fatty acid composition (Bjørndal et al, 2013;Leveille, Tillotson, & Sauberlich, 1963). The amino acid composition of the diet has been shown to influence lipogenesis and desaturation, as tyrosine down-regulates hepatic D6 activity (Peluffo, Nervi, Gonzalez, & Brenner, 1984), and arginine and leucine can regulate the gene expression of Scd1 and Fas in muscle and adipose tissue (Madeira et al, 2014). Here, the amino acid composition did not differ to a large extent since they were all dominated by amino acids from casein.…”
Section: Discussionmentioning
confidence: 82%
“…‘Sustained juiciness until swallow’ was positively correlated with SFA and C18:0 and negatively correlated with C14:1 in LM. Madeira et al () reported that juiciness was positively correlated with C16:1 and negatively correlated with C18:2. Correlations between fatty acid composition, tenderness and palatability of pork should be investigated further to shed light on the multitude of other factors that may affect sensory traits.…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of FAME in liver was performed using a gas chromatograph Agilent Technologies 7890A (Agilent Technologies, Santa Clara, CA, USA), equipped with a flame ionisation detector (GC‐FID) and a Supelcowax™ 10 capillary column (30 m × 0.20 mm i.d., 0.20 μm film thickness; Supelco, Bellefonte, PA, USA). Gas chromatographic conditions and fatty acid identification are described in detail in Madeira et al . The quantification of total FAME was done using nonadecanoic acid (19:0) as the internal standard.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that some feeding strategies, such as reduced protein diets and amino acids supplemented diets improve fat partitioning in pigs . Betaine is a naturally occurring tertiary amine (trimethyl glycine) in most living organisms formed by the oxidation of choline .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation